Honeycomb-structured perovskite hollow fibre membranes with ultra-thin densified layer for oxygen separation - Liu, N.; Tan, X.; Meng, B.; Liu, Shaomin (Pergamon, 2011)
New honeycomb-structured and gas-tight La0.6Sr0.4Co0.2Fe0.8O3- α (LSCF) perovskite hollow fibre membranes have been developed with an ultra-thin dense layer using phase inversion/sintering technique with an EtOH–NMP mixture as the internal coagulant. By varying the rate of internal precipitation the surface morphology of the hollow fibre could be altered to provide a single thin dense layer and high support surface area. These membranes were able to provide significantly higher O2 fluxes than conventional types, with an improvement factor up to 15 at 800 °C, while maintaining membrane quality and mechanical stability.